Analisis Operasional Sistem Distribusi Tegangan Menengah ke Tegangan Rendah di Gardu Induk Serang - Iman, Dede Fauzul; Khaerunnisa, Putri; Fitri, Hanifah Mutiara; Aribowo, Didik (Universitas Batanghari Jambi, 2024)
Electrical energy is one of the main resources that is very much needed in everyday life and is an important indicator of a country's progress. The electric power distribution system plays an important role in ensuring efficient and reliable energy supply to consumers. Electricity distribution starts from power plants, through transmission and distribution networks, until it reaches the end consumer. This distribution process involves various components, such as substations, power transformers, and distribution lines that adjust the voltage according to consumer needs. This study aims to analyze the operation of the distribution system from medium voltage to low voltage at the Serang Main Substation, with a focus on reducing power losses, improving distribution quality, and minimizing system disruptions. The research methods used include literature studies, observations of existing distribution systems, and interviews with experts in the field of electricity distribution. The results of the study show that distribution efficiency can be improved with better load management, capacitor installation, and the application of modern technology in the distribution network. Thus, a more efficient electric power distribution system can provide significant benefits to consumers and energy providers, reduce power losses, and improve overall system reliability.